Perspektif Pendidik dan Tenaga Kependidikan (PTK) di Kabupaten Blitar terkait Kepatuhan Protokol Kesehatan di Sekolah - Rahayenda Ivory Puryono; Anna Wahyuni Widayanti; Susi Ari Kristina (Faculty of Pharmacy, Universitas Gadjah Mada, 2023)
Educators and Education Personnel (EEP) are one of the priorities that take precedence in the stages of the vaccination program as a form of preventing the spread of COVID-19. In August 2022, there were cases of exposure to COVID-19 where the first program reached 86%, the cause was compliance with implementing health protocols. This study aims to determine the level of compliance in implementing the COVID-19 prevention health protocol and identify the factors that influence the level of compliance. This research is a quantitative non-experimental study with a cross-sectional study approach. Questionnaires were distributed to 522 EEP by purposive sampling, 339 EEP respondents were obtained with a response rate of 64.94%, divided into 290 EEP as research samples and 49 samples used for the reliability test. Data collection was carried out in September-November 2022 using an online questionnaire via the GoogleTM form. A reliable questionnaire was used with a Cronbach's α value 0.864. The results were tested of normality then analyzed by using the JAMOVI application. For parametric data, the student t-test was used, while for non-parametric data, Mann-Whitney and Kruskal-Wallis data were used. Spearman correlation is used to determine the factors that influence the level of EEP compliance. As results the level of EEP health protocol compliance was 67.9% in the medium category. Factors that influence the level of PTK compliance are the organizational environment (p-value 0.001) and self-efficacy (p-value 0.001). Meanwhile, the level of knowledge (p-value 0.093) showed no significant correlation on the level of EEP compliance.